The Efficiency Of Service Delivery Mechanisms Of Metropolitan Municipalities In South Africa - Khumalo, Musawakhe (Graduate School of Business (GSB), 2024)
Municipalities in South Africa continue to struggle with service delivery because they lack the personnel, resources, and leadership to provide residents with timely, highquality service. The study examined whether inefficiencies exist in the delivery channels of services to Metropolitan Municipality of South Africa; and also examine the effect of these modes of delivery of service delivery on returns to scale (constant and variable). The modes of delivery are in-house and outsourcing. The input-oriented method was applied to examine whether inefficiencies exist; while panel data regression was applied to determine the effect. The results show that inefficiencies exist in service delivery within some municipalities; both in input and output. The city of Johannesburg and Ekurhuleni recorded the highest slacks in output efficiency across all four services; while Mangaung was the most efficient in water, electricity and solid waste delivery with the least or no output slacks. The mode of delivery generally had a negative significant effect on service delivery with electricity topping the ranks in terms of inefficiency.